Learning of Social Studies in The Principles of Developing Powerful Learning - Hendry Alfiani Ari Sandi (Social Studies Conference Proceedings, 2022)
This article aims to describe how to shape the characteristics of students to become excellent and intelligent citizens. Therefore, one way to achieve this goal is to apply influential social studies learning. Powerful social studies learning is a learning process that has principles to improve and develop social studies learning outcomes. Powerful Social Studies learning helps students develop an understanding of being good citizens and able to assume their civic responsibilities. Influential social studies learning is a learning process with principles to improve and develop learning outcomes. Powerful social studies learning contains principles on what educators should know, what to do, and what they must possess, which are applied by five principles. Social studies learning and learning must be meaningful, integrative, value-based, challenging, and active learning (Learning is Active). Of the five principles, educators quickly develop the learning process so that students can receive understanding logically and critically, curiosity, problem-solving, and skills in their social environment.